Direct-write non-linear photolithography for semiconductor nanowire characterization. - Parkinson, P; Jiang, N; Gao, Q; Tan, H; Jagadish, C (IOP Publishing, 2012)
A practical bottleneck prohibiting the rapid, confident and damage-free electrical contacting of vapour-liquid-solid grown nanowires arises from the random spatial distribution and variation in quality of the nanowires, and the contact dimensions required. Established techniques such as electron-beam lithography or focused ion-beam deposition have challenges in scaling, damage or complexity that can make a large statistical sample difficult. We present a direct laser-writing technique to allow rapid electrical contacting of nanowires on a large variety of substrates.